Intestinal Secretion Induced by Vasoactive Intestinal Polypeptide: A COMPARISON WITH CHOLERA TOXIN IN THE CANINE JEJUNUM IN VIVO - Krejs, Guenter J. (1978)
The effect of vasoactive intestinal polypeptide (VIP) on intestinal water and electrolyte transport and transmucosal potential difference was investigated in the dog jejunum in vivo and compared to secretion induced by cholera toxin. Isolated jejunal loops were perfused with a plasma-like electrolyte solution. VIP (0.08 μg/kg per min) was administered directly into the superior mesenteric artery by continuous infusion over 1 h. From a dye dilution method, it was estimated that a mean plasma VIP concentration of 12,460 pg/ml reached the loops. VIP caused secretion of water and electrolytes; for example, chloride: control, 8 μeq/cm per h absorption; VIP, 92 μeq/cm per h secretion. A marked increase in transmucosal potential difference (control, −1.0 mV; VIP, −5.9 mV, lumen negative) occurred within 1 min after starting VIP infusion. Analysis of unidirectional fluxes showed increased plasma-to-lumen flux of sodium and chloride and decreased lumen-to-plasma flux of sodium. Chloride and bicarbonate were actively secreted against an electrochemical gradient. Although sodium secretion occurred down an electrochemical gradient, flux ratio analysis suggested a component of active sodium secretion. VIP caused a slight increase in protein output into the loops; light microscopy revealed capillary dilatation and closed intercellular spaces. The effect of VIP was readily reversible. Except for the delayed onset of secretion, the effect of cholera toxin was qualitatively similar to VIP; however, capillary dilatation and increased protein output were not noted with cholera toxin.